Practical Guide to Paraphilia and Paraphilic Disorders - Balon, Richard (Springer International Publishing : Imprint: Springer, 2016)
This book is a concise, practical guide to both paraphilia and paraphilic disorders as defined by the DSM-5 guidelines. Written by experts in the field, the chapters cover the different types of paraphilic disorder as well as the cutting-edge, emerging issues such as online sex. Unlike any other book on the market, the text also covers the most successful treatment strategies, include the therapeutic, hormonal, and psychopharmacological approaches. The book also discusses the ethical, legal, and cultural issues that are common complications when dealing with paraphilic disorders. Many chapters feature an introduction, diagnostic criteria, summary of evidence, clinical example, recommendations, conclusion, and references. Practical Guide to Paraphilia and Paraphilic Disorders is a valuable resource for psychiatrists, psychologists, residents, and all medical professionals working with patients who may suffer from paraphilia and/or paraphilic disorders.